Efecto de antiparasitarios vitaminas y hormonas sobre la carga endoparasitaria y parámetros productivos en bovinos - Cedeño Cruzzati, Pierina Michelle (2023)
This study evaluated the effect of antiparasitic, vitamins and hormones on the parasite load and productive parameters in cattle at the San Vicente farm in Pujilí. Three treatments were applied (T1): (Day 0) antiparasitic; (Day 30) vitamins; (Day 60) antiparasitic; (Day 90) growth hormones; (T2): (Day 1) energy supplements and antiparasitic; (Day 30) growth hormones; (Day 60) antiparasitic; (Day 90) vitamin supplements, and a control treatment (T0), to review their variability, a completely randomized block design plus covariance was developed under assumptions of analysis of variance and its similar non-parametric, additionally the Tukey test at 5% was applied to compare the averages. In the results, T2 (use of ivermectin and albendazole) obtained the greatest effect by achieving the lowest endoparasite load in steers at 90 and 120 days with 811 eggs per gram (hpg) p value = <0.049 and (566 hpg) p value = <0.034 respectively. No significant differences (p>0.05) were found between treatments in relation to monthly and final weight of the animals, but, T2 showed higher average weight gains from day 60 (46.89 kg), day 90 (68.22 kg) and in the final weight (83.00 kg), In addition, it was established that T2 is more profitable than the other treatments. The findings suggest that the use of the implemented variations reduces parasitic load and generates weight gains, however, it is necessary to evaluate other parameters of performance in cattle.